Twilight [videorecording (DVD)] - Hardwicke, Catherine; Stewart, Kristen, 1990-; Pattinson, Robert, 1986-; Burke, Billy; Kendrick, Anna; Reed, Nikki, 1988-; Lautner, Taylor, 1992-; Meyer, Stephenie, 1973- (Meyer, Stephenie, 1973- Twilight saga, 2010)
Isabella Swan moves to gloomy Forks, Washington to live with her father. She begins her junior year in high school and becomes fascinated by Edward Cullen. He holds a dark secret which is only known by his family. To Edward, Bella is what he has waited 90 years for, a true soul mate. But he knows the further they progress in their relationship the more he is putting Bella and those close to her at risk. Edward tries to warn Bella that she should leave him, but she refuses.